Prevalence and risk factor analysis for post-partum depression in women: a cross-sectional study at tertiary care centre - Rani, Kanchan; Nandi, Nupur; Parmar, Seema Singh; Rathore, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Postpartum depression (PPD) is non-psychotic depressive episode that occurs between postpartum to fourteen months of childhood. It has adverse effect on mother and child health. Aim of this study was to analyze prevalence and risk factors for postpartum depression at tertiary care centre. Methods: This cross-sectional study was done in obstetrics and gynaecology department where 175 women between 10 days to 1 year of delivery were assessed using Edinberg postpartum depression scale. A score of 10 or more were taken as sign of postpartum depression. Various socio-demographic and obstetrics variables were assessed using SPSS (Statistical Package for the Social Sciences). Results: Prevalence of PPD was found in 11.4% patients. Common risk factors associated were intrauterine death (IUD) or early neonatal death, postpartum complications and lack of family support. Conclusions: Postpartum is common among postnatal women and is associated with various factors which can be modified. So early detection of associated risk factors is needed for early intervention and prevents its impact on mother and child health.